NATIONAL INCOME IN THE PERSPECTIVE OF ISLAMIC ECONOMICS - Nur Afkarina, Diva; Rahmawati, Nora (LPPM Universitas KH. A. Wahab Hasbullah, 2019)
Knowing national income from a traditional and economic perspective. This study examines Islam in detail. The purpose of this study is to determine the understanding of national income, the Islamic economic perspective on the national approach, and the factors that affect the national approach. Literature research and reasoning techniques are the strategies used in this research. The basis of discussion in the research is literature review and several works. According to the results of this study, the national income of a country is the total national income of a country, entered in society in a country within one year. Also receive public salaries Estimates using indicators such as (Gross Domestic Product) or wages. Gross public income (GNI), a measure of the value of all labor and products within the territory of a country or by residents of a country. Sources of national income from the point of view of Islamic economics are ghanimah, zakat, sadaqah, infaq, ushr, jizyah, kharaj, mining tax, and waqf. Interest and total supply, utilization and reserve funds, and investment are factors that affect wages.